PENGARUH FAKTOR-FAKTOR KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN (STUDI KASUS : KA BANDARA STASIUN SUDIRMAN BARU, BNI CITY) - Agus Wahyono; Sari Fatmaningsih (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2019)
This research aims is to understand; 1) the influence of tangible toward to customer satisfaction, 2) the influence of reliability toward to customer satisfaction, 3) the influence of tresponsiveness toward to customer satisfaction, 4) the influence of assurance toward to customer satisfaction, 5) the influence of empathy toward to customer satisfaction, 6) the influence of tangible, reliability, responsiveness, assurance & empathy toward to Customer satisfaction airport train at Sudirman Baru Station (BNI City). This research is done by conducting survey. The population of this research are consumers who have used it airport train at Sudirman Baru Station (BNI City). The sampling method done by non probability sampling technique with the sample of 60 people. The data collect method obtained by questionnaires which validity and reliability has been tested. Multiple regression are applied to answer the hypothesis as the analysis method. The result of this research indicate that; 1) there is influence of tangible has a negative on customer satisfaction, 2) there is influence of reliability has a negative on customer satisfaction, 3) there is influence of responsiveness has a negative on customer satisfaction, 4) there is influence of assurance has a negative on customer satisfaction, 5) there is influence of empathy has a positive on customer satisfaction